Macroscopic spray characteristics of wide distillation fuel (WDF). (1st January 2017) - Yu, Wenbin; Yang, Wenming; Mohan, Balaji; Tay, Kun Lin; Zhao, Feiyang
Highlights: Spray behaviours of piezoelectric and solenoid injectors were compared. The effects of fuel pressure fluctuation on multiple injections were illustrated. With a piezoelectric injector, the spray optical experiment has been done. The spray characteristics of WDF were investigated. Abstract: In this study, the performance of piezoelectric and solenoid injectors were compared. With a piezoelectric injector, the spray characteristics of kerosene and G50 (gasoline/diesel blend fuel), which are kinds of WDF, were investigated and compared to diesel. The characteristics such as spray penetration, spray velocity, spray angle and air entrainment were used to understand the spray behaviour of the test fuels. The results indicate that the piezoelectric injector shows significant improvement over the conventional solenoid injector in injection response and needle opening speed, which enables precise and rapid control of injection. The trade-off effects of charge density and injection pressure on spray penetration and spray velocity are quite clear, while spray angle is almost insensitive to injection pressure. Kerosene and G50 give smaller but similar spray penetration and velocity compared to diesel. The spray angle of kerosene and G50 are larger compared to diesel. The spray volume and mass of entrained air for kerosene and G50 are higher compared to diesel, which indicates kerosene and G50 can form better fuel–air mixing, which is very important for the performance of engine when fuelled by WDF.